2023
DOI: 10.1002/pc.27772
|View full text |Cite
|
Sign up to set email alerts
|

Interface engineering of carbon fiber composites using CNT: A review

Renuka Sahu,
Sathiskumar A. Ponnusami,
Christian Weimer
et al.

Abstract: This paper aims to explore the potential of carbon nanotubes (CNTs) in enhancing the structural capability and multifunctionality of carbon fiber composites in aerospace applications, primarily by focusing on interfacial applications. The conventional method of dispersing CNTs in a matrix is not fully efficient in exploiting the mechanical and multifunctional performance of CNTs. Hence, the use of CNTs at the interface or as a coating on the surface of carbon fibers has been suggested as a means of achieving m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 227 publications
0
5
0
Order By: Relevance
“…By now, it was reported that graphene oxide (GO), 12,13 Mxene, 14 as well as carbon nanotubes (CNTs) 15–17 have been widely applied in surface modification of fibers to improve mechanical properties of corresponding composites. Damacena et al 18 revealed that GO‐modified CF could improve the interfacial adhesion between CF and PA6, and PA6/CF composites containing 0.5 wt% GO showed the best tensile and bending properties.…”
Section: Introductionmentioning
confidence: 99%
“…By now, it was reported that graphene oxide (GO), 12,13 Mxene, 14 as well as carbon nanotubes (CNTs) 15–17 have been widely applied in surface modification of fibers to improve mechanical properties of corresponding composites. Damacena et al 18 revealed that GO‐modified CF could improve the interfacial adhesion between CF and PA6, and PA6/CF composites containing 0.5 wt% GO showed the best tensile and bending properties.…”
Section: Introductionmentioning
confidence: 99%
“…Nanocomposites, composed of a polymer matrix with nanoscale conductive fillers, have received notable attention as highly advanced and functional materials 1–4 . Among the various nanoscale conductive fillers currently available, carbon nanotubes (CNTs) are particularly promising due to their high electrical conductivity and aspect ratio values, forming electrically conductive pathways in nanocomposites 2,5–8 . These remarkable properties of CNTs enable CNT‐incorporated nanocomposites to exhibit outstanding electrical performance, even at low CNT contents 7,9–11 …”
Section: Introductionmentioning
confidence: 99%
“…These properties 32 include high electrical and thermal conductivity, superior tensile strength, flexibility, and elasticity. 33,34 Above all, since CNTs are carbon derivatives, they are able to absorb microwave radiation and turn it into heat with very high efficiency. [35][36][37][38] When microwaves are applied to the CNT-reinforced polymer matrix, an internal temperature gradient is produced.…”
Section: Introductionmentioning
confidence: 99%